Preparation Mechanism and Experimental Results on Deep Thermophilic and Halotolerant Solids-free Drilling Fluids - Sun, Haoyang; Xin, Yinchang; Hu, Yang (Asian Journal of Chemistry, 2012)
A new deep thermophilic and halotolerant solids-free drilling fluid was prepared by adding the modified polysaccharide, xanthan gum and the common sulfonated phenolic resin. It was characterized by high temperature resistance, high shear force resistance and good stability in high salinity. It also had low fluid loss and low price. At the same time, the mechanism of action and coordination of polysaccharide and xanthan gum was also described in this paper.